RASA PENYESALAN PADA REMAJA PELAKU SEKS PRANIKAH SETELAH TERKENA SANKSI PIDANA DI LPKA KELAS II KOTA TOMOHON - Rinna Yuanita Kasenda; Dandi Mustafa Syam Hamid; Aprillia Sriwangi Kansil; Jonathan Ray Melo (Jurnal Genta Mulia, 2024)
This article aims to determine the remorse of teenage perpetrators of premarital sex after being subjected to criminal sanctions. A qualitative approach is used to analyze the perpetrator's self-management and the strategies used to face the next life. The research method uses qualitative methods. Research instruments: Observation and direct interviews were carried out to gather information without giving a traumatic feeling. The research results showed that the perpetrator felt regret and was traumatized by his actions. In conclusion, support from parents, friends and the environment is very necessary in dealing with feelings of trauma and regret due to juvenile delinquency such as premarital sex.